Long-term outcomes from upgrade to cardiac resynchronisation therapy in ischaemic versus non-ischaemic heart disease: original scientific paper - Yücel, Gökhan; Stoesslein, Karolina; Gaasch, Leo; Kodeih, Abbass; Oeztuerk, Oezge Nur; Hetjens, Svetlana; Yazdani, Babak; Pfleger, Stefan; Liebe, Volker; Rudic, Boris; Behnes, Michael; Langer, Harald; et al. (Acta cardiologica, 2023)
Cardiac resynchronisation therapy (CRT) can be necessary in patients with chronic heart failure, who have already been provided with transvenous cardiac implantable electrical devices. Upgrade procedures revealed controversial results, while long-term outcomes regarding underlying Ischaemic- (ICM) or Non-Ischaemic heart disease (NICM) have yet to be described. The Mannheim Cardiac Resynchronisation Therapy Registry (MARACANA) was designed as a retrospective observational single-centre registry, including all CRT implantations from 2013-2021 (n = 459). CRT upgrades (n = 136) were retrospectively grouped to either ICM (n = 84) or NICM (n = 52) and compared for New York Heart Association classification (NYHA), paced QRS-width, left ventricular ejection fraction (LVEF), tricuspid annular plane systolic excursion (TAPSE) and other heart failure modification aspects in the long-term (59.3 ± 5 months). Baseline-characteristics including paced QRS-width, upgrade indications or NYHA-classification were comparable for both groups (group comparison p>.05). The CRT upgrade improved NYHA (ICM: 2.98 ± 0.4 to 2.29 ± 0.7, NICM: 2.94 ± 0.5 to 2.08 ± 0.5) and the LVEF (ICM: 27.2 ± 6.6 to 38.25 ± 8.8, NICM: 30.2 ± 9.4 to 38.7 ± 13.8%) after five years, irrespective of underlying heart disease (each group p < .05, group comparison p>.05). Only ICM revealed significant improvements in TAPSE (15.9 ± 4.1 to 18.9 ± 4.1 mm) and narrowing of the paced QRS-width (185.4 ± 29 to 147.2 ± 16.3 ms) after five years (each p < .05). Upgrade to CRT might improve heart failure symptoms and left-ventricular systolic function in the long-term, irrespective of underlying ischaemic or non-ischaemic heart disease.
Gesehen am 06.03.2024